Identification maps for selected sky fields with IR/radio sources constructed at the base of CCD observations at the Andrushivka Astronomical Observatory - Perekhod, O.V.; Andruk, V.M.; Pakuliak, L.K.; Ivashchenko, Yu.M. (Кинематика и физика небесных тел, 2005)
In July 2002 the CCD unfiltered images of eight sky areas with the IR/radio sources from ICRF 1732+389, 1803+784, 1807+698, 1845+797, 1943+228, 2023+335, 2223–052, and 2229+695 were obtained with the Zeiss-600 telescope of the Andrushivka Observatory. This telescope is equipped with a CCD S1C-017 detector; our observations were carried out in integral light only. The processing of images was implemented by the MIDAS/ROMAFOT software. Coordinates and magnitudes down to B = 21 mag in 3'×3' fields were obtained in the USNO A2.0 system. Identification maps in integral light obtained as the result of the CCD image processing are shown.